Carotid artery stenting and improvement of cognitive function in patients with asymptomatic carotid artery stenosis - Filipa Jácome; Joel Sousa; Armando Mansilha (Angiologia e Cirurgia Vascular, 2024)
INTRODUCTION: Several studies unveiled an association between asymptomatic carotid artery stenosis and cognitive impairment, questioning the “asymptomatic” nature of carotid stenosis. Although there is increasing evidence of the impact of carotid artery stenting (CAS) on cognition, the current literature still contains some unclear data and conflicting results. This study aimed to examine the impact of CAS on various domains of cognitive function in patients with asymptomatic carotid artery stenosis.